2014
DOI: 10.5935/0103-507x.20140006
|View full text |Cite
|
Sign up to set email alerts
|

Use of scores to calculate the nursing workload in a pediatric intensive care unit

Abstract: ObjectiveTo assess the performance of the Nursing Activities Score in a pediatric intensive care unit, compare its scores expressed as time spent on nursing activities to the corresponding ones calculated using the Simplified Therapeutic Intervention Scoring System, and correlate the results obtained by both instruments with severity, morbidity and mortality.MethodsProspective, observational, and analytical cohort study conducted at a type III general pediatric intensive care unit. The study participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
5
0
5
Order By: Relevance
“…The PICU NAS results (morning: 60.4% and night: 58.4%) are substantially similar to other studies in pediatric intensive care units [53,55].…”
Section: Discussionsupporting
confidence: 87%
“…The PICU NAS results (morning: 60.4% and night: 58.4%) are substantially similar to other studies in pediatric intensive care units [53,55].…”
Section: Discussionsupporting
confidence: 87%
“…A research that sought to identify the NW in different nurseries belonging to a neonatal Unit, listed according to the severity of patients at low risk, medium risk, high risk and isolation, showed that the NAS mean was proportional to the complexity of care (11) . Another study with the same objective in a Pediatric ICU, found NAS mean greater than 56% (17) . Both allow inference that the greater the complexity, the greater the nursing workload.…”
Section: Discussionmentioning
confidence: 98%
“…The results reveal that the workload, obtained by NAS score, varied from 56 to 94%, which corresponds, respectively, to 13.38 and 22.53 hours of nursing assistance to the patient in a 24-hour period. Other studies conducted in Brazil point a mean pediatric ICU workload of 50% (18)(19) .…”
Section: Discussionmentioning
confidence: 95%